A Testing Coverage Based SRGM Subject to the Uncertainty of the Operating Environment - Sujit Kumar Pradhan; Anil Kumar; Vijay Kumar (Computer sciences & mathematics forum, 2023)
The number of software failures, software reliability, and failure rates can be measured and predicted by the software reliability growth model (SRGM). SRGM is developed and tested in a controlled environment where the operating environment is different. Many SRGMs have developed, assuming that the working and developing environments are the same. In this paper, we have developed a new SRGM incorporating the imperfect debugging and testing coverage function. The proposed model’s parameters are estimated from two real datasets and compared with some existing SRGMs based on five goodness-of-fit criteria. The results show that the proposed model gives better descriptive and predictive performance than the existing selected models.